Comparative Study of Gold and Carbon Nanoparticles in Nucleic Acid Lateral Flow Assay - Juan Carlos Porras; Mireia Bernuz; Jennifer Marfa; Arnau Pallares-Rusiñol; Mercè Martí; María Isabel Pividori (Nanomaterials, 2021)
A lateral flow assay (LFA) is a paper-based, point-of-need test designed to detect a specific analyte in complex samples in low-resource settings. Although LFA has been successfully used in different applications, its use is still limited when high sensitivity is required, especially in the diagnosis of an early-stage condition. The limit of detection (LOD) is clearly related to the signal-generating system used to achieve the visual readout, in many cases involving nanoparticles coupled to a biomolecule, which, when combined, provides sensitivity and specificity, respectively. While colloidal gold is currently the most-used label, other detection systems are being developed. Carbon nanoparticles (CNPs) demonstrate outstanding features to improve the sensitivity of this technology by producing an increased contrast in the paper background. Based on the necessity of sensitivity improvement, the aim of this work is a comparative study, in terms of analytical performance, between commercial streptavidin gold nanoparticles (streptAv-AuNPs) and avidin carbon nanoparticles (Av-CNPs) in a nucleic acid lateral flow assay. The visual LOD of the method was calculated by serial dilution of the DNA template, ranging from 0.0 to 7 pg μL−1/1.5 × 104 CFU mL−1). The LFA achieved visual detection of as low as 2.2 × 10−2 pg μL−1 using Av-CNPs and 8.4 × 10−2 pg μL−1 using streptAv-AuNPs. These LODs could be obtained without the assistance of any instrumentation. The results demonstrate that CNPs showed an increased sensitivity, achieving the nanomolar range even by visual inspection. Furthermore, CNPs are the cheapest labels, and the suspensions are very stable and easy to modify.